Land Degradation Surveillance Framework Based Data - International Center for Tropical Agriculture; International Livestock Research Institute; Mekelle University (International Food Policy Research Institute, 2019)
The data included in this study were collected as a part of 'situation analysis' based on landscape characteristics and condition. The data were collected in four Africa RISING sites?Basona, Michew, Jawe, and Sinana?across four regions simultaneously with the soil sampling exercise.